Complement inhibition by soluble complement receptor type 1 improves microcirculation after rat liver transplantation - Lehmann, Thorsten G.; Koeppel, Thomas; Kirschfink, Michael; Gebhard, Martha-Maria; Herfarth, Christian; Otto, Gerd; Post, Stefan (Transplantation, 1998)
Recent observations provide evidence the complement is involved in the pathophysiology of ischemia/reperfusion injury. In this study, we assessed the impact of complement inhibition on hepatic micro-circulation and graft function using a rat model of liver transplantation.Methods Arterialized orthotopic liver transplantation was performed in Lewis rats after cold preservation (University of Wisconsin solution, 4°C, 24 h). Eight animals received the physiological complement regulator soluble complement receptor type 1 (sCR1) intravenously 1 min before reperfusion. Controls received Ringer's solution (n=8). Microvascular perfusion, leukocyte adhesion, and Kupffer cell phagocytic activity were studied 30-100 min after reperfusion by in vivo microscopy.Results.Microvascular perfusion in hepatic sinusoids was improved in the sCR1 group (87±0.7% vs. 50±1%; P<0.001). The number of adherent leukocytes was reduced in sinusoids (68.3±4.7 vs. 334.1±15.8 [adherent leukocytes per mm ≤ liver surface]; P<0.001) and in postsinusoidal venules after sCR1 treatment (306.6±21.8 vs. 931.6±55.9 [adherent leukocytes per mm ≤ endothelial surface]; P<0.001). Kupffer cell phagocytic activity was decreased in the sCR1 group compared to controls. Postischemic bile production reflecting hepatocellular function was increased by almost 200% (P=0.004) after complement inhibition. Plasmatic liver enzyme activity was decreased significantly upon sCR1 treatment, indicating reduced parenchymal cell injury.Conclusions.Our results provide further evidence that the complement system plays a decisive role in hepatic ischemia/reperfusion injury. We conclude that complement inhibition by sCR1 represents an effective treatment to prevent reperfusion injury in liver transplantation.